The adoption of Web 2.0 technologies in academic libraries: A comparative exploration - Williams, Marion Lucille (Journal of Librarianship and Information Science, 2020)
This paper addresses the adoption and non-adoption of communication methods such as social media and explores the implementation of Web 2.0 technologies and their use in academic libraries. I interviewed 16 library employees from six academic university libraries in the Flanders region of Belgium and in South Africa. I explored five academic university libraries in the urban regions of Flanders and South Africa and one situated in a rural region of South Africa. This article discusses the benefits of using social media as a communication tool to engage with students. The results demonstrate that ‘ease of use’ was portrayed as a beneficial construct and has a positive influence on behavioural intention and use of Web 2.0 technologies. A comparison on the adoption of social media between the two countries indicate that financial resources, infrastructure and management support are crucial determining factors in service delivery.
Article published in the Journal of Librarianship and Information Science 2020, Vol. 52(1) 137–149 DOI: 10.1177/0961000618788725
Keywords: Academic libraries; Belgium; Social media user engagement; South Africa; Web 2.0; Library 2.0; Academic libraries; Technological innovations; Academic libraries- Use studies